Pengaruh Self-Efficacy Terhadap Resiliensi Akademik Siswa - Tiara Prawitasari; Eni Rindi Antika (Jurnal Bimbingan dan Konseling Indonesia, 2022)
Abstract: The purpose of this study was to determine the effect of self-efficacy on the academic resilience of 7th grade students of SMP Negeri 3 Kendal in dealing with hybrid learning. This study used a quantitative ex post facto design. The population in this study amounted to 201 7th grade students of SMP Negeri 3 Kendal. The research sample is 127 class 7th students taken by simple random sampling technique. The research instrument used is the self-efficacy and academic resilience scale. This study uses two data analysis technique, namely descriptive analysis and simple regression analysis. Student’s self-efficacy is in the moderate category (M= 100,929) and student’s academic resilience is in the moderate category (M = 100,819). The results showed that self-efficacy has an effect on academic resilience with a coefficient of determination (R2 = 0,549, ρ < 0,05). This means that self-efficacy contributes to academic resilience by 54,9%, while the rest is influenced by other factors. Keywords: self-efficacy, academic resilience, hybrid learning